Effective Methods of Using the Medicinal Plant, Plantago Major, In Modern Medicine - Zakriddinov Ilyosjon Ilhomjon oglu; Mamadaliyev Daniyor Shojalil oglu; Abdurakhmanova Khaticha Rakhimjon kizi (American Journal of Biology and Natural Sciences, 2025)
Today, the concept of integrating modern medicine and traditional medicine is gaining popularity in a number of countries, and it is believed that integrative medicine may be the medicine of the future. There is a lot of evidence to support such opinions, and we can also take as an example the emergence of new diseases as a result of the negative effects of chemical drugs. It is known that traditional medicine, with its unique traditions, is used to ensure the health of the population, provide medical and sanitary assistance, in particular, in the prevention of chronic diseases, and in their treatment, it is recommended to use medicinal plants that have passed many tests in practice in terms of quality, safety and effectiveness. Among such plants, Zubturum is a very useful medicinal plant.